Diagnostic Accuracy of Infection Markers to Diagnose Infections in Neonates and Children Receiving Extracorporeal Membrane Oxygenation - Doo, Irene; Staub, Lukas P.; Mattke, Adrian; Haisz, Emma; Seidler, Anna Lene; Alphonso, Nelson; Schlapbach, Luregn J. (Frontiers in Pediatrics, 2022)
Background: Infections represent one of the most common complications in patients managed on Extracorporeal Membrane Oxygenation (ECMO) and are associated with poorer outcomes. Clinical signs of infection in patients on ECMO are non-specific. We assessed the diagnostic accuracy of Procalcitonin (PCT), C-reactive protein (CRP) and White cell count (WCC) to diagnose infection on ECMO. Methods: Retrospective single centre observational study including neonates and children <18 years treated with ECMO in 2015 and 2016. Daily data on PCT, CRP and WCC were assessed in relation to microbiologically confirmed, and clinically suspected infection on ECMO using operating characteristics (ROC) curves. Results: 65 ECMO runs in 58 patients were assessed. CRP had the best accuracy with an area under the ROC curve (AUC) of 0.79 (95%-CI 0.66-0.92) to diagnose confirmed infection and an AUC of 0.72 (0.61-0.84) to diagnose confirmed and suspected infection. Abnormal WCC performed slightly worse with an AUC of 0.70 (0.59-0.81) for confirmed and AUC of 0.66 (0.57-0.75) for confirmed and suspected infections. PCT was non-discriminatory. Conclusion: The diagnosis of infections acquired during ECMO remains challenging. Larger prospective studies are needed that also include novel infection markers to improve recognition of infection in patients on ECMO.